Предмет: Математика,
автор: Аноним
(x - 1 15/16) + 7 3/16 = 8 1/16 + 4 9/16
Ответы
Автор ответа:
0
(x - 1 15/16) + 7 3/16 = 8 1/16 + 4 9/16
(x - 1 15/16) + 7 3/16 = 12 10/16
(x - 1 15/16) = 12 10/16 - 7 3/16
(x - 1 15/16) = 5 7/16
x = 5 7/16 + 1 15/16
x = 6 22/16
x = 7 6/16
(x - 1 15/16) + 7 3/16 = 12 10/16
(x - 1 15/16) = 12 10/16 - 7 3/16
(x - 1 15/16) = 5 7/16
x = 5 7/16 + 1 15/16
x = 6 22/16
x = 7 6/16
Похожие вопросы
Предмет: Математика,
автор: afanasijarhipov841
Предмет: Қазақ тiлi,
автор: bekkalievbekarys0
Предмет: Английский язык,
автор: gulnurmeldebek2003
Предмет: Алгебра,
автор: няша3333